ANALYSIS OF RIVER CLEANING SHIP DESIGN USING THE TRASHER BOAT IDEA USING MAXSURF: - - Sinamoi, Syamsuri Alpha Joshua; Sabri, Muhammad (Talenta Publisher, 2023)
Ships are a means of transportation for moving materials and goods from one place to another. Along with this increase, it was also followed by the development of other industries so that it had an impact. However, in increasing these activities, in addition to generating benefits, it also creates new impacts through the waste produced. Several work boats are made to solve problems related to the type of work according to needs. The solution that can be used to overcome the accumulation of garbage in the river is to use the help of a Trash Skimmer Boat. This work boat is a type of special ship that is used to carry out waste collection in rivers, lakes, seas and canals. By using the help of Maxsurf Software, the main size is L = 100 cm, B = 30 cm H = 15 cm, T = 3.54 cm with a payload capacity of 3 kg. It has the following data: Displacement = 6,968 kg ; block coefficient (Cb) = 0.387; Prismatic Coef (Cp) = 0.832. Keyword : Ship, Workboat, Trasher boat, Trash Skimmer Boat